Penetration Value of KPR Rent-To-Own Based on The Capability of Low-Income Community in Buying a House - Dewi, Paraditha Mutia; Herlina, Lien; Shalihati, Fithriyyah (Business Review and Case Studies, 2025)
Background: Capstone project activities carried out at PT Bank Tabungan Negara (Persero) Tbk (BTN) revealed the challenges currently faced by the housing industry. The high backlog rate has prompted BTN to innovate a new home financing scheme known as Rent-To-Own Mortgage (KPR RTO), but its sales have not yet been widespread, especially among low-income communities (MBR). Purpose: This study aims to identify the existing value of the KPR RTO, examine the characteristics and capabilities of low-income communities, and formulate value penetration strategies to aid in the development of the KPR RTO. Design/methodology/approach: This study used qualitative methods through semi-structured in-depth interviews and focus group discussions with purposive sampling. Interview questions were designed to align with the 5C Principle and SOAR Analysis for targeted strategy formulation.Findings/results: The results of the study indicate that the capabilities of low-income communities in purchasing homes are limited due to income constraints and difficult administrative requirements. Conclusion: The results of the low-income community capability analysis were carried out to help formulate a value penetration strategy so that this KPR RTO product could be well received by the market because its value is based on market needs. Originality/value (State of the art): The author recommends four value penetration strategies: Introduction, Pre-rent, Rent, and Retrieve. Keywords:  banking, capability, credit, MBR, value penetration